Sustainability strategy : the case of logistics service providers - Lim, Jun Ming. (2012)
Logistics service providers are beginning to understand that sustainability can be a great source of competitive advantage and those who manage to translate sustainability into sources of differentiation will emerge as winner in this new competitive landscape. Accordingly, many have devised and implemented some sort of sustainability strategy. Unfortunately, the quest to sustainability is not always smooth-sailing and problems often arise as a result of inadequate stakeholders’ participation in sustainability-related decision-making and sustainability strategy not being developed within business context. This paper thus seeks to explore and analyze how participation from different stakeholder groups may affect the outcome of sustainability strategy and how this is affected by the level of integration between business strategy and sustainability strategy. Through a survey conducted among 96 logistics service providers and the use of Structural Equation Modeling technique, full information maximum likelihood, it is shown that higher level of participation from internal and value chain stakeholders can lead to better integration between business strategy and sustainability strategy. In addition, it was established that the level of integration positively correlates with sustainability performance. The findings shed light on what managers and public officials can do to help logistics service providers achieve better sustainability performance.